A kind of intelligent information aggregate and its preparation method and application
By combining carbon-cured materials with radio frequency identification materials to prepare intelligent information aggregates, the problem of difficult traceability of material sources and poor compatibility of RF tags in concrete structures is solved, and the effect of high mechanical properties and strong signal transmission is achieved, which improves the management level of concrete.
Patent Information
- Application Number
- CN202310062338.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-01-14
AI Technical Summary
In the prior art, when a concrete structure has quality problems during service, the source of the concrete material it uses is difficult to trace, making it difficult to control the engineering quality. At the same time, the RFID tag has poor compatibility with concrete, which affects mechanical properties and signal transmission.
Intelligent information aggregate is prepared by combining carbon-cured materials with radio frequency identification materials. The mineralization reaction between carbon-cured materials and carbon dioxide is generated to generate mineralized products, and composited with radio frequency identification materials to form intelligent information aggregates with high mechanical strength and information carrier functions.
It realizes good compatibility between intelligent information aggregate and concrete, improves the mechanical properties and signal transmission strength of concrete, and significantly improves the management level of concrete during production and use.
Smart Images

Figure BDA0004061403640000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of intelligent building materials, and in particular relates to an intelligent information aggregate and a preparation method and application thereof. Background Art
[0002] Concrete products, prefabricated components, cast-in-place structures, etc. generate a large amount of information that needs to be recorded during the preparation, maintenance, transportation, and use of concrete products. The traditional manual recording method is labor-intensive and inefficient. At the same time, when quality problems occur in concrete structures during service, the source of the concrete materials used is difficult to trace, making it difficult to control the quality of the project. Some studies have used radio frequency tags to store concrete product information, embed the tags inside the products, and read the information in the tags through radio frequency identification technology. However, radio frequency identification tags are generally encapsulated with organic materials such as epoxy resins. These organic materials have poor compatibility with concrete, resulting in a significant reduction in the mechanical properties of concrete. At the same time, organic materials also have a large attenuation of radio frequency signals, resulting in low received signal strength. There are also radio frequency tags that are pasted on the surface of concrete for use. However, organic materials have poor weather resistance, resulting in a reduced service life of radio frequency tags. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an intelligent information aggregate and a preparation method and application thereof. The intelligent information aggregate provided by the present invention has little effect on the mechanical properties of concrete and has a high information carrier function.
[0004] To achieve the above object, the present invention is implemented through the following technical solutions:
[0005] A smart information aggregate, comprising a carbon-cured material, a radio frequency identification material, a magnetic absorber, a modifier, a reinforcing agent, a water reducer and water; based on a single portion of radio frequency identification material, the mass ratios of the carbon-cured material, the magnetic absorber, the modifier, the reinforcing agent, the water reducer and water are: (7.6-64): (1.2-5.6): (0.8-7.2): (0.24-2.8): (0.15-1.2): (1.5-10.5).
[0006] Preferably, the modifier is one or more of amorphous siliceous materials, hydroxypropyl methylcellulose, carboxymethyl cellulose, pure acrylic emulsion, and acrylic emulsion. The modifier can improve the homogeneity of the mixture, improve the bonding ability of the mixture with the radio frequency identification material, and further improve the mechanical strength of the smart information aggregate and the compatibility with concrete, and reduce the impact on the mechanical properties of the concrete structure.
[0007] Preferably, the carbon solidified material is one or more of tricalcium silicate, γ-type dicalcium silicate, β-type dicalcium silicate, monocalcium silicate, tricalcium disilicate, calcium hydroxide, magnesium hydroxide, calcium oxide, and magnesium oxide, or one or more of solid wastes with the above minerals as main components, and the particle size of the carbon solidified material is 5 to 150 μm.
[0008] Preferably, the radio frequency identification material includes a radio frequency chip and a radio frequency antenna connected to the radio frequency chip. The radio frequency chip has a unique identification number, which can be written with information to be stored or marked, and the radio frequency antenna can be detected by an external reader / writer, thereby transmitting the information stored in the radio frequency chip. The operating frequency of the external reader / writer includes a low frequency of 30 to 300 kHz, a high frequency of 3 to 30 MHz, and an ultra-high frequency of 433 to 950 MHz.
[0009] Preferably, the magnetic absorber includes one or more of ferrite powder, iron powder, iron alloy powder, aluminum borosilicate, and the particle size of the magnetic absorber is less than 45 μm. The magnetic absorber can improve the anti-metal interference ability of the intelligent information aggregate, so that the external reader can receive a higher signal strength.
[0010] Preferably, the reinforcing agent includes one or more of chitosan, polyacrylamide, polyethylene glycol, and polyvinyl alcohol. The reinforcing agent can induce the formation of more carbonate minerals in the mineralization reaction and improve the compactness of the smart information aggregate blank.
[0011] Preferably, the water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent, and the water reducing rate is ≥20%.
[0012] The present invention also provides a method for preparing the above-mentioned intelligent information aggregate, comprising the following steps:
[0013] The carbon solidified material, the magnetic wave absorbing agent, the modifier, the reinforcing agent, the water reducing agent and water are mixed in proportion to obtain a mixture;
[0014] Filling the mixture and the RFID material into a mold and forming the aggregate body;
[0015] After the aggregate body is dehydrated, it is placed in a carbon dioxide atmosphere for mineralization to obtain intelligent information aggregate.
[0016] Preferably, the above-mentioned molding process is compression molding or casting molding.
[0017] Preferably, the temperature for controlling the water of the aggregate body is 40-60°C, and the moisture content of the aggregate body after water control is 10%-20%; the pressure of the carbon dioxide atmosphere is 0.1-0.3MPa, the volume concentration of carbon dioxide is 20%-99.9%, the mineralization temperature is 5-90°C, and the mineralization time is 2-24h.
[0018] The present invention also provides an application of the above-mentioned intelligent information aggregate in concrete products, prefabricated components or cast-in-place structures, which is convenient for quality control, information management or product traceability.
[0019] The beneficial effects of the present invention are:
[0020] The present invention utilizes the mineralization reaction of carbon solidified materials with carbon dioxide to generate mineralized products mainly composed of calcium carbonate and magnesium carbonate, and composites them with radio frequency identification materials to prepare intelligent information aggregate, while giving it high mechanical strength and information carrier function. Different from organic materials, the calcium carbonate or magnesium carbonate formed by the mineralization reaction of carbon solidified materials has a shell-like gradient structure with better mechanical properties, so the strength of the intelligent information aggregate is higher; on the other hand, inorganic minerals such as calcium carbonate or magnesium carbonate are more compatible with the main body of concrete, so when the intelligent information aggregate is pre-buried in the concrete, it can perfectly form a concrete skeleton structure, which reduces the mechanical properties of the concrete less.
[0021] The technical principle of the invention is simple and the effect is obvious. It can significantly improve the management level of concrete during production and use, while ensuring that the main body of the concrete structure has high mechanical properties. It has broad application prospects in quality control, information management, product traceability, etc. of concrete products, prefabricated components, and cast-in-place structures. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The present invention provides an intelligent information aggregate, comprising a carbon-cured material, a radio frequency identification material, a magnetic absorber, a modifier, a reinforcing agent, a water reducer and water; based on a single portion of radio frequency identification material, the mass ratios of the carbon-cured material, the magnetic absorber, the modifier, the reinforcing agent, the water reducer and the water are: (7.6-64): (1.2-5.6): (0.8-7.2): (0.24-2.8): (0.15-1.2): (1.5-10.5).
[0024] Unless otherwise specified, the technical means used in the present invention are conventional means well known to those skilled in the art, and the materials used are all commercially available products.
[0025] The present invention is based on a single portion of radio frequency identification material, and the carbon curing material is preferably 40 to 64 parts, the magnetic absorber is preferably 3.6 to 5.6 parts, the modifier is preferably 3.2 to 7.2 parts, the reinforcing agent is preferably 1.8 to 2.8 parts, the water reducer is preferably 0.9 to 1.2 parts, and the water is preferably 7.2 to 10.5 parts.
[0026] The present invention also provides a method for preparing the above-mentioned intelligent information aggregate, comprising the following steps:
[0027] The carbon solidified material, magnetic absorber, modifier, reinforcing agent, water reducing agent and water are uniformly mixed in proportion to obtain a mixture; the mixture is filled into a mold, and the radio frequency identification material is placed at the center of the mold, and an aggregate blank is obtained by pressing or casting; the aggregate blank is water-controlled at a temperature of 40 to 60° C. until the moisture content is 10% to 20%, and then the aggregate blank after water control is placed in a carbon dioxide atmosphere for mineralization reaction, the pressure of the carbon dioxide atmosphere is controlled to be 0.1 to 0.3 MPa, the volume concentration of carbon dioxide is 20% to 99.9%, the temperature of the mineralization reaction is 5 to 90° C., preferably 25 to 90° C., and the mineralization time is 2 to 24 hours, preferably 12 to 24 hours, to obtain an intelligent information aggregate.
[0028] The shape of the aggregate blank of the present invention is not limited, and can be a regular shape such as a cylinder, a square, a disc, etc., or an irregular shape, and it only needs to customize a mold of a corresponding shape.
[0029] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0030] Example 1
[0031] The carbon solidifying material is γ-type dicalcium silicate with a particle size of less than 150 μm, the magnetic absorber is iron powder with a particle size less than 45 μm, the modifier is carboxymethyl cellulose, the reinforcing agent is chitosan, and the water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent with a water reducing rate of ≥20%.
[0032] In parts by weight, 40 parts of γ-type dicalcium silicate, 3.6 parts of iron powder, 3.2 parts of carboxymethyl cellulose, 1.8 parts of chitosan, 0.9 parts of polycarboxylic acid-based high-efficiency water reducer, and 7.2 parts of water are taken. γ-type dicalcium silicate, iron powder, carboxymethyl cellulose, chitosan, polycarboxylic acid-based high-efficiency water reducer and water are mixed evenly to obtain a mixture; the mixture is filled into a 15mm×15mm×15mm cubic mold, and 1 part of radio frequency identification material is placed in the center of the mold, wherein the radio frequency identification material is made of Alien H3 radio frequency chip and aluminum etched radio frequency antenna encapsulated by FR4 glue; then the aggregate blank is prepared by casting molding; the aggregate blank is placed in a 50°C oven to control the moisture content to 15%, and the aggregate blank after water control is placed in a carbon dioxide atmosphere for mineralization to obtain intelligent information aggregate, the mineralization gas pressure is 0.2MPa, the temperature is 25°C, the relative humidity is 50%, the carbon dioxide volume concentration is 99.9%, and the time is 12h.
[0033] Example 2
[0034] The only difference from Example 1 is that the carbon-cured material is 24 parts of γ-type dicalcium silicate and 40 parts of monocalcium silicate, the magnetic absorber is 5.6 parts of iron powder, the modifier is 7.2 parts of acrylic emulsion, the reinforcing agent is 2.8 parts of polyethylene glycol, the water reducer is 1.2 parts of polycarboxylic acid-based high-efficiency water reducer, and water is 10.5 parts. The rest is the same as Example 1.
[0035] Example 3
[0036] The only difference from Example 1 is that the carbon solidifying material is 7.6 parts of monocalcium silicate, the magnetic absorber is 1.2 parts of iron powder, the modifier is 0.8 parts of hydroxypropyl methylcellulose, the reinforcing agent is 0.24 parts of chitosan, the water reducer is 0.15 parts of polycarboxylic acid-based high-efficiency water reducer, and water is 1.5 parts. The rest is the same as Example 1.
[0037] Comparative Example 1
[0038] Fill epoxy resin into a 15mm×15mm×15mm cubic mold, and place the same radio frequency identification material as in Example 1 at the center of the mold, prepare an aggregate blank by casting, and place the aggregate blank in a 50°C oven for curing; wait until the epoxy resin is completely cured to obtain epoxy resin aggregate.
[0039] Comparative Example 2
[0040] The only difference from Example 1 is that no magnetic absorber is added to the mixture for preparing the intelligent information aggregate, and the rest is the same as Example 1.
[0041] Comparative Example 3
[0042] The only difference from Example 1 is that no modifier is added to the mixture for preparing the intelligent information aggregate, and the rest is the same as Example 1.
[0043] Performance Testing:
[0044] Take 3 pieces of each smart aggregate prepared in each embodiment and comparative example, test its compressive strength, and calculate the average compressive strength. Pre-embed 3 pieces of each of the smart information aggregate prepared in the embodiment and the aggregate prepared in the comparative example into the center of a C60 concrete test block. The concrete test block has a size of 100mm×100mm×100mm and is placed in a standard curing box for 28 days. Test the compressive strength of the concrete test block containing the smart information aggregate, and calculate its average compressive strength. The compressive strength is tested in accordance with the national standard "GB / T50081-2002 Standard for Test Methods for Mechanical Properties of Ordinary Concrete".
[0045] The information stored in the intelligent information aggregate inside the concrete is read by an external reader / writer. The working frequency of the external reader / writer is 433-950MHz ultra-high frequency. The signal strength of the external reader / writer is recorded. The closer the signal strength value is to 0, the stronger the received signal is. If the signal strength value is within -50dBm, it means that the received signal is strong and the signal attenuation is small. The test results are shown in Table 1.
[0046] Table 1 Performance test results of intelligent information aggregate prepared in the embodiment and the comparative example
[0047]
[0048] It can be seen from the above table that the intelligent information aggregate prepared by the present invention has higher compressive strength and signal strength than the comparative example.
[0049] Compared with Example 1, the intelligent information aggregate prepared by the present invention has higher mechanical strength than epoxy resin aggregate. When the intelligent information aggregate is pre-buried in the center of the concrete test block, the reduction value of the concrete compressive strength does not exceed 6MPa, indicating that the intelligent information aggregate of the present invention has good compatibility with concrete and has little effect on the mechanical properties of concrete. The signal strength of the external reading and writing machine of each embodiment is within -50dBm, while the signal strength of the external reading and writing machine of Comparative Example 1 exceeds -65dBm, indicating that the intelligent information aggregate prepared by the present invention has excellent signal transmission performance and low signal strength attenuation.
[0050] Compared with Comparative Example 2, Example 1 has better signal strength and mechanical properties, indicating that the magnetic absorber improves the compressive strength while improving the anti-metal interference ability.
[0051] Compared with Comparative Example 3, Example 1 has higher signal strength and mechanical properties, indicating that the modifier can improve the homogeneity of the mixture, improve the bonding ability between the mixture and the radio frequency identification material, and thus improve the mechanical strength of the smart information aggregate. At the same time, the higher the mechanical strength, the denser the aggregate structure, and therefore the stronger the signal strength obtained by the reading machine.
[0052] In summary, the present invention utilizes carbon solidified material, magnetic absorber, modifier, reinforcing agent, water reducer and water to form a mixture, and pre-buries radio frequency identification material, and produces mineralization reaction in a carbon dioxide atmosphere to prepare smart information aggregate, which not only makes it have good mechanical properties, but also has little effect on the compressive strength of concrete when it is buried in concrete, and also has high signal strength.
[0053] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0054] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An intelligent information aggregate, characterized in that: It includes carbon-cured material, radio frequency identification material, magnetic wave absorber, modifier, reinforcing agent, water reducer and water; based on a single portion of radio frequency identification material, the mass ratio of the carbon-cured material, magnetic wave absorber, modifier, reinforcing agent, water reducer and water is: 40:3.6:3.2:1.8:0.9:7.2; the carbon-cured material is γ-type dicalcium silicate; the modifier is carboxymethyl cellulose; the magnetic wave absorber is iron powder, and the particle size of the magnetic wave absorber is less than 45μm; the reinforcing agent is chitosan.
2. The intelligent information aggregate according to claim 1, characterized in that: The particle size of the carbon solidified material is 5-150 μm.
3. The intelligent information aggregate according to claim 1, characterized in that: The radio frequency identification material includes a radio frequency chip and a radio frequency antenna connected to the radio frequency chip.
4. The intelligent information aggregate according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent with a water reduction rate of ≥20%.
5. The method for preparing the intelligent information aggregate according to any one of claims 1 to 4, characterized in that: The following steps are involved: The carbon solidified material, the magnetic wave absorbing agent, the modifier, the reinforcing agent, the water reducing agent and water are mixed in proportion to obtain a mixture; Filling the mixture and the radio frequency identification material into a mold, and forming the mold to obtain an aggregate blank; After the aggregate blank is dehydrated, it is placed in a carbon dioxide atmosphere for mineralization to obtain the intelligent information aggregate.
6. The method for preparing the intelligent information aggregate according to claim 5, characterized in that: The water control temperature is 40-60°C, and the moisture content of the aggregate body after water control is 10%-20%; the pressure of the carbon dioxide atmosphere is 0.1-0.3MPa, the volume concentration of carbon dioxide is 20%-99.9%, the mineralization temperature is 5-90°C, and the mineralization time is 2-24h.
7. Use of the intelligent information aggregate according to any one of claims 1 to 4 in concrete products, prefabricated components or cast-in-place structures.
Citation Information
Patent Citations
Prefabricated carpet type intelligent asphalt pavement and preparation method thereof
CN110396884A
Mineralization-based self-sensing building skin as well as preparation method and application thereof
CN115259774A